Exploring the Islamic tradition for resonance and dissonance with cognitive therapy for depression - Thomas, Justin; Ashraf, Saquab (2011)
Many of the defining principles and techniques used within contemporary cognitive therapy are congruent with basic Islamic values, and in some cases they are highly resonant with specific Islamic directives aimed at shaping human cognition and behaviour. Several previous authors concur on this point, suggesting a particularly good fit between cognitive therapy and the Islamic tradition relative to other forms of psychotherapeutic intervention. This paper explores the process of cognitive therapy and the models of depression upon which it is based, highlighting areas of resonance and dissonance with Islamic thought. The paper advocates the development of cognitive behavioural psychotherapeutic content and technique informed by Islamic tradition. We argue that such spiritually and culturally attuned interventions, in many cases, will be more appropriate and clinically effective for clients with world views shaped by Islam.
Keywords: Islam; cognitive therapy; Depression